Rancang Bangun Trainer Digital Berbasis Field Programmable Gate Array - Sihombing, Berlian; Mardianto, Eko; Ilyas Hadikusuma, Mohd; Chandra, Yudi; Ridhwan Sufandi, Muhammad; Satriyo, Satriyo (Electrical Network Systems and Sources, 2023)
In modern times, aspects of life have developed increasingly rapidly, especially in the field of electronics and technology. Where there are various components that can be programmed digitally,which includes Field Programmable Gate Array, which has been widely developed and studied. Thesystem to be operated is the basic logic gate, running led, flip flop, dc motor and stepper. The materialdiscussed in the trainer system programming is about counters, ring counters, and buffers. This trainerhelps the student learning system in designing digital systems that will program a system using a programlanguage, namely the VHDL language.